A Survey on Shiraz Health Care Center Personnel's Knowledge and Attitudes Toward the Consumption of Probiotic Products in 2018 - Aliasghar Masihi Nezhad; Amena Barikani; Maryam Javadi (Shiraz University of Medical Sciences, 2022)
Background: Probiotics are non-pathogen microorganisms that confer a health benefit on the gut system. The Health personnel are responsible for treating the patients, which is a sensitive role; therefore, their knowledge, attitude, and consumption of probiotics are important. Methods: A cross-sectional study was planned to evaluate personnel. Random sampling was conducted to select 136 persons as study samples from 275 personnel willing to participate in the study. Data collected using a self-made questionnaire consisted of demographic data, awareness, attitude, and behavioral items. Descriptive, correlation, and regression statistics were performed using SPSS ver. 22. Results: Total awareness score of personnel about probiotics was medium. No significant associations were found between total awareness score and gender, education, and field of education (P>0.050) except for age (P=0.008) and acquaintance (P=0.003). The younger group and experienced participants were more aware of probiotics than others. Most of the personnel had positive attitudes about probiotics. The study showed no correlation between attitude and variables, including genus (P=0.150), education (P=0.507), field of study (P=0.756), and acquaintance of personnel (P=0.259). The personnel's overall behavior score did not correlate with genus (P=0.841), age (P=0.955), education level (P=o.527), field of study (P=0.955), and acquaintance (P=0.832). Logistic regression indicated that total awareness predicts personnel's behavior. Conclusion: Shiraz health centers Personnel had no considerable awareness about probiotics. Personnel's attitudes toward probiotics were positive, but lack of knowledge, high price, and limited access to probiotic products resulted in low consumption.